2014
DOI: 10.1111/anec.12206
|View full text |Cite
|
Sign up to set email alerts
|

QRS‐T Angle: A Review

Abstract: For proper distribution of preventative resources, a more robust method of cardiac risk stratification should be encouraged in addition to merely reduced ejection fraction. To this end the QRS-T angle, an electrocardiogram (ECG)-derived measure of the difference in mean vectors of depolarization and repolarization, has been found associated with sudden cardiac death and other mortal and morbid outcomes in multiple observational studies over the past decade. The use of both frontal and spatial QRS-T angle in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
214
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(230 citation statements)
references
References 30 publications
7
214
0
9
Order By: Relevance
“…The spatial mean QRS-T angle reflects the spatial angle between depolarization and repolarization and was calculated as [18]:…”
Section: Quantitative Evaluationmentioning
confidence: 99%
“…The spatial mean QRS-T angle reflects the spatial angle between depolarization and repolarization and was calculated as [18]:…”
Section: Quantitative Evaluationmentioning
confidence: 99%
“…SAI QRST was calculated as the arithmetic sum of areas under the QRS‐T curve 15, 17. Spatial mean QRS‐T angle was measured as the 3‐dimensional angle between the mean QRS‐vector and the mean T‐vector 9. The magnitude, azimuth, and elevation of the SVG vector were measured as previously defined 12…”
Section: Methodsmentioning
confidence: 99%
“…SVG is a vector sum of spatial QRS and T vectors, reflecting implication of the spatial QRS‐T angle 9. Spatial QRS‐T angle is a well‐known marker9 of the risk of ventricular tachyarrhythmias10 and sudden cardiac death (SCD)11, 12 in the general population, heart failure (HF) patients, and other populations 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the spatial QRS-T angle is an important prognostic predictor and that it is superior to more conventional ECG parameters. While it is known that the spatial QRS-T angle varies with age and gender [5], to our knowledge there is less information available regarding dependence on race. The present study compares the normal limits of the spatial QRS-T angle in four cohorts of apparently healthy, different racial groups.…”
Section: Introductionmentioning
confidence: 98%